1973
DOI: 10.1073/pnas.70.5.1509
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Structure, and Absolute Configuration of a New Natural Insect Juvenile Hormone from Manduca sexta

Abstract: Two juvenile hormones are isolated from organ cultures of corpora allata of the tobacco hornworm moth, Manduca sexta Johannson, and are purified by high-resolution liquid chromatography. These are identified as methyl (2E, 6E)-(IOR)-10,11-epoxy-3,7,11-trimethyl-2,6-dodecadienoate, a new natural hormone, and methyl (2E,6E) -(IOR,11S) -10,11 -epoxy -3,7,11 -trimethyl- Continued improvements in insect tissue culture techniques have led to their increased use in studies of endocrine physiology (5). Indirect indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

1973
1973
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(54 citation statements)
references
References 15 publications
2
52
0
Order By: Relevance
“…Chiral HPLC separation of the 10R and 10S enantiomers of JH III conclusively showed that CYP15A1 has a very high degree of selectivity in the epoxidation of methyl farnesoate, producing the natural 10R enantiomer. The absolute configuration is known for the JH III produced by the CA of Manduca sexta and Tenebrio molitor (21)(22)(23), and for the JH III produced enzymatically with L. migratoria and B. giganteus CA microsomes (9,18).…”
Section: Expression Of Cyp15a1 In the Cockroach: Tissue And Developmementioning
confidence: 99%
“…Chiral HPLC separation of the 10R and 10S enantiomers of JH III conclusively showed that CYP15A1 has a very high degree of selectivity in the epoxidation of methyl farnesoate, producing the natural 10R enantiomer. The absolute configuration is known for the JH III produced by the CA of Manduca sexta and Tenebrio molitor (21)(22)(23), and for the JH III produced enzymatically with L. migratoria and B. giganteus CA microsomes (9,18).…”
Section: Expression Of Cyp15a1 In the Cockroach: Tissue And Developmementioning
confidence: 99%
“…This has been accomplished by culturing active prothoracic glands of Manduca sexta in vitro and analyzing the incubation medium by a variety of chemical and biological techniques; a similar approach has proved successful in elucidating the structure of the M. sexta juvenile hormones (13). Since Fukuda's classical experiments (1) on the commercial silkworm, Bombyx mori, it has been generally accepted that the hormone responsible for initiating the moulting process in all insects is the secretory product of the prothoracic glands (or analogous structures).…”
mentioning
confidence: 99%
“…In addition, good incorporation of the epoxy acid derived from JH I, has been witnessed in H. cecropia, although it may not be an obligatory intermediate (8). However, no information has been available on biosynthesis of the carbon skeletons of the juvenile hormones, except for a slight incorporation of [2-'4C]acetate (7), and a complete lack of incorporation of methionine in the chain of homoterpenoids JH I (7) and JH II (6,7).…”
mentioning
confidence: 99%